Cancer stem cells in oral squamous cell carcinoma. Literature review - Rodríguez-Vargas, Mariana Paulina (2022)
Objective: To perform a literature review on oral squamous cell carcinoma, the presence of cancer stem cells; their association with the course of the disease and therapeutic applications. Methods: A search was performed in the PubMed database by entering the following algorithm: ((((neoplastic stem cells[MeSH Terms]) OR (Cancer stem cells[Text Word])) AND (Squamous Cell Carcinoma of Head and Neck[MeSH Terms])) AND (Oral squamous cell carcinoma[Text Word]), to find articles in english published between 2012 and 2022. The PRISMA diagram was used to identify and select the articles. Results: A result of 49 articles was obtained; of which 27 were chosen according to the title and abstract in their association with the topic. In addition, 8 additional articles suggested by their relationship with the information previously searched were included. In total, 35 articles were evaluated. There has been found that tumoral cells in squamous oral carcinoma are heterogeneous since they include cancer stem cells wich possess characteristics of stem and neoplasic cells; which possess characteristics of stem cells as well as neoplastic cells; they have been associated with disease progression, recurrence, and metastasis and have been considered to be a key mechanism of therapy failure. Conclusions: The expression of stem cell markers in oral squamous cell carcinomas has been demonstrated and has contributed to their identification in oral squamous cell carcinomas and has been implicated in the behavior of cancer cells. New therapeutic measures aimed at eliminating cancer stem cells have been proposed and developed.